The Main Causes Of Illegal Immigration And Algeria’s Strategy To Combat This Phenomenon - Akilal, Nassim (University of Eloued جامعة الوادي, 2024)
Abstract: One of the issues that have captured the attention of governments and the general public is illegal immigration. It causes concern because, as a result of the difficulties that follow, it has taken center stage in many nations, adversely affecting their stability and security. In order to stop and deal with this phenomenon, nations are actively working to determine its root causes. Similar to other countries, Algeria has devised several tactics and methods, primarily focusing on the human security approach, to reduce the incidence of undocumented immigration. Algeria has attempted to tackle this situation by utilizing a variety of techniques, including legal, security, and economic measures.
Keywords: Illegal immigration; crime; security; refugees; border